Maternal mental health in the first year postpartum in a large Irish population cohort: the MAMMI study - Daly, Deirdre; Higgins, Agnes; Begley, Cecily; Hannon, Susan (My University, 2022)
Purpose: The international perinatal literature focuses on depression in the postpartum period. Prevalence and pathways of depression, anxiety and stress from pregnancy through the first postpartum year are seldom investigated. Methods: MAMMI is a prospective cohort study of 3009 first-time mothers recruited in pregnancy. Depressive, anxiety and stress symptoms measured using the Depression, Anxiety and Stress Scale (DASS 21) in pregnancy and at 3-, 6-, 9- and/or 12-months postpartum. Results: Prevalence of depressive and stress symptoms was lowest in pregnancy, increasing to 12-months postpartum. Anxi- ety symptoms remained relatively stable over time. In the first year after having their first baby, one in ten women reported moderate/severe anxiety symptoms (9.5%), 14.2% reported depression symptoms, and one in five stress symptoms (19.2%). Sociodemographic factors associated with increased odds of postpartum depression, anxiety and stress symptoms were younger age and being born in a non-EU country; socioeconomic factors were not living with a partner, not having postgraduate education and being unemployed during pregnancy. Retrospective reporting of poor mental health in the year prior to pregnancy and symptoms during pregnancy were strongly associated with poor postpartum mental health. Conclusions: The current findings suggest that the current model of 6-week postpartum care in Ireland is insufficient to detect and provide adequate support for women’s mental health needs, with long-term implications for women and children.
PUBLISHED
Keywords: Perinatal mental health; Depression; Anxiety; Stress; ANTENATAL DEPRESSION; ANXIETY; Depression; POST PARTUM; POSTNATAL DEPRESSION; POSTPARTUM DEPRESSION; Perinatal Mental Health; Women's health postpartum; mental health; perinatal mental health; Mental Health/Psychosocial disability; Health